Proceedings of the 2nd International Conference on Social, Applied Science, and Technology in Home Economics (ICONHOMECS 2019) 2020
DOI: 10.2991/assehr.k.200218.019
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Thermal Comfort of Woolpeach Modest-Fashion Products: A Case Study in Indonesia

Abstract: Woolpeach is a type of fabrics made of 100% polyester with best-selling record in Indonesian market. Muslims form the largest population in Indonesian, and it is not surprising that they wear modest-fashion, usually made of woolpeach fabrics, in performing their daily activities. Therefore, this research wants to know thermal comfort of woolpeachwhen used in creating modest-fashion products in relation to tropical climate of Indonesia. This research used three indicators to know thermal comfort of the modest f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It can be concluded that most students could perform the stages of fashion production properly and follow the procedure. Prahastuti et al (2020) addressed that a fashion product can be considered comfortable if the clothing is made proportionally to suit the user. The fashion production stage embodies the designs created by students, and every step must be done carefully with the proper techniques to produce perfect clothes.…”
Section: Difficulty At the Fashion Production Stagementioning
confidence: 99%
“…It can be concluded that most students could perform the stages of fashion production properly and follow the procedure. Prahastuti et al (2020) addressed that a fashion product can be considered comfortable if the clothing is made proportionally to suit the user. The fashion production stage embodies the designs created by students, and every step must be done carefully with the proper techniques to produce perfect clothes.…”
Section: Difficulty At the Fashion Production Stagementioning
confidence: 99%
“…The use of modest clothing has become popular in recent decades (Zabeen et al 2017). Muslim clothing or hijab has even become an expensive high-end fashion concept (Prahastuti et al 2020). Therefore, the Muslim fashion or hijab market must implement a variety of more effective strategies to be able to support the development of the Muslim fashion industry (Rai 2018).…”
mentioning
confidence: 99%